Hepatitis A and E Viruses Are Important Agents of Acute Severe Hepatitis in Asia: A Narrative Review - Reina Sasaki-Tanaka; Tatsuo Kanda; Takeshi Yokoo; Hiroyuki Abe; Kazunao Hayashi; Akira Sakamaki; Hiroteru Kamimura; Shuji Terai (Pathogens)
Acute-on-chronic liver failure (ACLF) and acute liver failure (ALF) are severe hepatitis that occur in patients with and without chronic liver diseases and/or cirrhosis, respectively, and both often result in death. Hepatitis A virus (HAV) and hepatitis E virus (HEV) infection can cause these severe conditions. We reviewed the role of HAV and HEV, which infect humans through the fecal–oral route, in ALF and ACLF in Asian countries. This narrative review was the derived from a traditional non-systematic review. Hepatitis A should be recognized as one of the sexually transmitted infections, especially among men who have sex with men. HAV genotype IIIA infection seems to present a more severe clinical manifestation. Acute HEV-1 infection is associated with ALF in pregnant women in India. HEV-4, rather than HEV-3, was found in severe hepatitis in Japan. HEV also plays a role as a cause of acute insult and/or chronic liver disease in immunocompromised patients with ACLF. Further studies are needed for the development of vaccines and antivirals against HAV and HEV infections. Despite the limitations of the recording of cases and the extent of specific vaccinations, multidisciplinary cooperation, involving hepatologists, virologists, experts in public health, etc., may improve the treatment of HAV and HEV infection.